Factors Affecting Nutritional Problems Of Elementary School Students - Dwi Siyamsih (PT. Anagata Sembagi Education, 2024)
These nutritional issues are serious problems that affect public health globally. Deficiencies in certain nutrients such as iron, vitamin A, vitamin D or folic acid can lead to various health problems. In the study of factors affecting the nutritional problems of primary school students, researchers can use various research methods to understand the relationship between the factors that contribute to the nutritional problems. Observational Studies, Case Control Studies, These studies help in identifying risk factors that contribute to nutritional problems among primary school students. Secondary Data Analysis: Researchers can also use secondary data, such as national health survey data or school data, to analyze factors related to nutritional problems among primary school students. The results in this study show that the nutritional problems of primary school students are influenced by various factors, including home environment, nutrition knowledge, diet, access to nutrition resources, and nutrition education at school. Efforts to improve students' nutritional status require a holistic approach through interventions involving parents, schools and the community as a whole.